You should notice that the composition of the functions f and g is a linear function.

You need to remember how to compose two functions such that:

`(fog)(x) = f(g(x))`

Since `f(x) = 2x - 3` , you should substitute g(x) for x such that:

`f(g(x)) = 2g(x) - 3`

The problem provides the information that `f(g(x)) = 2x+1` , hence, you should set the equations 2g(x) - 3 and 2x+1 equal such that:

`2g(x) - 3 = 2x + 1 =gt 2g(x) = 2x + 1 + 3`

`2g(x) = 2x + 4`

Dividing by 2 yields:

`g(x) = x + 2`

**Hence, evaluating the function g(x) under the given conditions yields `g(x) = x + 2` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now